1998
DOI: 10.1080/03601239809373170
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and toxicological data in Fenthion and omethoate acute poisoning

Abstract: This study paper reports on two cases of poisoning with the organophosphorus insecticides, fenthion and omethoate. The two victims were admitted in the Intensive Care Unit (ICU) a few hours after ingestion of the two insecticides. They received appropriate treatment for organophosphorous poisoning (gastric lavage, activated charcoal, atropine and pralidoxime) and supportive care. Both patients survived. Organophosphate blood levels were determined on admission (fenthion 2.9 micrograms/ml, omethoate 1.6 microgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 1 publication
0
9
1
Order By: Relevance
“…However, given the tendency of harm with oximes observed in the current study, it is not clear if higher doses of oximes in humans would either offer benefits or increase harm. A high therapeutic level of oximes may still not be efficacious, as reports have demonstrated the occurrence of intermediate syndrome despite maintaining plasma levels of pralidoxime of Ͼ4 g/mL (37,38). Recent evidence from experimental animals also suggested that high-dose pralidoxime prolonged time to extubation and increased mortality in paraoxon-exposed minipigs (39).…”
Section: Discussionmentioning
confidence: 99%
“…However, given the tendency of harm with oximes observed in the current study, it is not clear if higher doses of oximes in humans would either offer benefits or increase harm. A high therapeutic level of oximes may still not be efficacious, as reports have demonstrated the occurrence of intermediate syndrome despite maintaining plasma levels of pralidoxime of Ͼ4 g/mL (37,38). Recent evidence from experimental animals also suggested that high-dose pralidoxime prolonged time to extubation and increased mortality in paraoxon-exposed minipigs (39).…”
Section: Discussionmentioning
confidence: 99%
“…One accidental oral intoxication with fatal outcome after 16 days occurred in Italy [19], but no case of suicidal omethoate ingestion has been reported so far. In one case of omethoate ingestion the patient, who recovered completely, showed an omethoate blood level of 1.6 µg/ml [20]. No additional data are available about omethoate concentrations in human body fluids or tissue samples in fatal poisoning cases.…”
Section: Discussionmentioning
confidence: 99%
“…17) This was probably because the onset of symptoms in fenthion poisoning is often delayed for up to several days after admission to hospital and the predominant toxicity is delayed onset of respiratory paralysis. 47,48) Therefore, in this study, we assessed the severity of patients on admission using two scoring systems (GCS and PSS), and then followed up with patient's clinical outcome (e.g., improved, discharged with severe morbidity or deceased) not only to find out the sensitivity of GCS and PSS scoring systems with the clinical outcome of poisoning, but also the correlation between GCS and PSS scoring systems.…”
Section: Prediction Of Severity By Two Scoring Systems and Their Relamentioning
confidence: 99%